Analisis Lingkungan Kerja Internal pada PT ASDP Indonesia Ferry - Muhammad Ray Gildan; Marsofiyati Marsofiyati; Ervina Maulida (Lembaga Pengembangan Kinerja Dosen, 2025)
In the socialization life at PT ASDP Indonesia Ferry every day is inseparable from the influence of the work environment created by individuals and groups, especially in the internal environment and problems that occur in the physical and non-physical environment. The purpose of this study is to analyze and find out how the internal work environment conditions are at PT ASDP Indonesia Ferry in physical and non-physical aspects. The research method used is a qualitative method that is descriptive in nature and data sources obtained by observing or interviewing employees at PT ASDP Indonesia Ferry with primary data collection consisting of pre-research and main research (observation, interviews and documentation). The results of this study are that the Company's internal work environment is still not optimal in supporting employee work, the most important internal work environment is company facilities, besides that the most important thing about the non-physical environment in this company is the work culture where this company adheres to an adhocracy work culture because it is dynamic and creative and psychological well-being.